2013
DOI: 10.1179/1743294412y.0000000110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent volume on properties of SnO2:Al films

Abstract: Aluminium doped tin oxide films (ATO) were deposited from starting solutions having different solvent volumes (10, 20, …, 50 mL), using a simplified spray pyrolysis technique and the effect of solvent volume on the structural, optical and electrical properties was investigated. Structural studies revealed that Al 3z incorporation into the Sn 4z sites of the SnO 2 lattice is gradually increased with increasing solvent volume. The variation in the preferential orientation factor f (110) as a function of solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…The overall lattice parameter is thus expected to decrease as more Al ions occupy the Sn sites, as indeed observed experimentally, see Figure 5b. Similar observations have been reported by Lee et al [27] for Al content in the film (atomic %) varing from 0 to 8.2%, Ravichandran et al [34] with Al concentration in the starting solution increasing from 0–30 atomic %, and Thirumurugan et al [43] for 3 atomic % doping. In addition, the broadening of the XRD peaks indicates a diminution of crystal sizes.…”
Section: Resultssupporting
confidence: 87%
“…The overall lattice parameter is thus expected to decrease as more Al ions occupy the Sn sites, as indeed observed experimentally, see Figure 5b. Similar observations have been reported by Lee et al [27] for Al content in the film (atomic %) varing from 0 to 8.2%, Ravichandran et al [34] with Al concentration in the starting solution increasing from 0–30 atomic %, and Thirumurugan et al [43] for 3 atomic % doping. In addition, the broadening of the XRD peaks indicates a diminution of crystal sizes.…”
Section: Resultssupporting
confidence: 87%
“…where Al Sn − represents the Sn 4+ site substituted by Al 3+ . A similar finding also has been reported by Thirumurugan et al 32 They also found a relatively low electron concentration for the low Al-doping concentration Al-doped SnO 2 (Al content between 6.7% and 13%) thin films. Again, it supports the above conclusion that the hole carriers generated by the Al 3+ −Sn 4+ substitution reactions would compensate free electrons generated by the intrinsic defects, i.e., oxygen vacancy.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…The hole carriers generated by the Al 3+ -Sn 4+ substitution reaction compensated for the free electrons contributed by the oxygen vacancies. 32 Thus, the electron carrier concentration of the n-type Al-doped SnO 2 thin films slightly decreased as the Al doping content increased. However, the hole carriers generated by the Al 3+ -Sn 4+ substitution were insufficient to convert the carrier polarity of the Al-doped SnO 2 thin films from n-type to p-type.…”
Section: Methodsmentioning
confidence: 95%